IMMUNOLOGY OF MULTIPLE SCLEROSIS - Uleng Bahrun; Chelvi Wijaya (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Multiple Sclerosis (MS) is an autoimmune disease that causes myelin destruction in the Central Nervous System (CNS). Characteristics of this disease are perivascular infiltration by inflammatory cells, demyelination and loss of axons, accompanied by multiple plaque formation in the brain and spinal cord. According to the National Multiple Sclerosis Society, 400,000 people suffer from MS in the United States and about 2.5 million people worldwide. The disease is usually diagnosed in patients aged 20-45 years and more often found in females than males with a ratio of 2: 1. Nevertheless, the etiology of MS is still unknown, but it is suspected that genetic and environmental factors may induce a response to central nervous system autoantigen, such as Epstein-Barr Virus (EBV) infection. It then causes edema, demyelination, axon destruction and loss of oligodendrosites, resulting in neurological deficits, plaque formation, scarring and reduced brain volume. Multiple sclerosis symptoms and signs actually vary greatly depending on the location of the lesions and the course of the various diseases. Multiple sclerosis, moreover, can be divided into four clinical categories, namely Clinically Isolated Syndrome (CIS), Relapsing Remitting Multiple Sclerosis (RRMS), Secondary Progressive Multiple Sclerosis (SPMS) and Primary Progressive Multiple Sclerosis (PPMS). Diagnosis of Multiple sclerosis is established based on clinical symptoms and supporting investigations, such as MRI, CSF and neurological examination. In CSF examination, oligoclonal bands are found in over 90% of patients, considered as one of the laboratory criteria supporting the diagnosis of MS. There are four kinds of drugs that have been approved by the FDA as disease modifying therapy for the initial treatment of MS patients, namely interferon beta-1a, subcutaneous (SC) interferon beta-1a, interferon beta-1b and glatiramer acetate  In conclusion, life expectancy in MS patients is only slightly reduced and survival is related to the disability occurred.